“Tungku Tigo Sajarangan”: Analisis Pola Komunikasi Kelompok dalam Interaksi Pemimpin Pemerintahan di Sumatera Barat - Gani, Rita (Mediator, 2006)
This article explores the meaning of triadic leadership interaction pattern found in Minangkabau culture of West Sumatera. Consisted of Ninik Mamak (Elders), Alim Ulama (Religious Leader), and Cerdik Pandai (Scholars and Intellectuals), the three party form the administration of Nagari—a cultural domain in Minangkabau discourse. Based on thesis research, it is found that each party is autonomously operated, though intensely interacted. The administration of Nagari has enliven the tradition called Tungku Tigo Sajarangan, which describe the harmonious relationship delivered through group communication among Elders, Religious Leaders, and Scholars.